Pengaruh Kompetensi dan Locus of Control Terhadap Kinerja Karyawan PLN (Persero) Unit Pelaksana Pembangkit Maluku - Ralahallo, Fransiska Natalia; Latupapua, Conchita. V.; Azzahra, Rachel Fatimah (KAMBOTI: Jurnal Sosial dan Humaniora, 2024)
This study explores the impact of competence and locus of control on employee performance at PT PLN (Persero) Maluku Power Generation Implementation Unit. The research aims to analyze how these factors contribute to employee performance. Utilizing a descriptive quantitative approach, the study included 35 employees as its population and employed SPSS 25 for data analysis using descriptive methods. The findings reveal that competence significantly influences employee performance, as indicated by a t-value exceeding the t-table and a significance level below the threshold (p < 0.05). Similarly, locus of control also demonstrates a significant positive effect on employee performance, supported by statistical results where the t-value exceeds the t-table, and the significance level is well within acceptable limits (p < 0.05). These results underscore the importance of enhancing employee competence and effectively managing locus of control to optimize performance.